TINJAUAN ARTIKEL: PENGOBATAN NON BEDAH PERI-IMPLANTITIS - Halim, Susanna; Florenly, Florenly; Winata, Mellisa; Luman, Marco; Leslie, Gloria Estefani (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2025)
Dental implants are materials inserted into the jawbone that serve as supports for restorations, resembling natural teeth. In addition to their aesthetic function, implants also play an important role in the rehabilitation of the stomatognathic system. Proper maintenance is essential for the long-term success of implant-based restorations. One of the common complications is peri-implantitis, a pathological condition characterized by inflammation of the peri-implant connective tissue and progressive loss of supporting bone. If left untreated, peri-implantitis can lead to implant failure. This study is a literature review aimed at evaluating the effectiveness of non-surgical treatment for peri-implantitis. Data were collected through a search on Google Scholar using relevant keywords, yielding 15,700 articles. After applying inclusion criteria, articles were selected that were published within the last five years (2020–2024), written in English, available in full text, and categorized as original research, reviews, or case reports. Findings from three case reports indicate that non-surgical approaches provide significant clinical improvements. In Case 1, after one year, probing depth reduced to 1.5–3 mm without bleeding. In Case 2, after six months, no signs of inflammation or further bone resorption were observed, with a 2.1 mm reduction in probing depth. In Case 3, after six months, inflammatory resolution was achieved, with probing depth reduced to 2 mm and increased bone level seen on radiographs. All patients demonstrated good oral hygiene, were non-smokers, and had no uncontrolled systemic diseases. Overall, non-surgical treatment for peri-implantitis can yield positive clinical outcomes in reducing probing depth and inflammation, especially in patients with good plaque control and stable systemic health. ABSTRAKImplan gigi merupakan bahan yang ditanam dalam tulang rahang dan berfungsi sebagai penyangga restorasi, dengan bentuk menyerupai gigi alami. Selain memiliki fungsi estetik, implan juga berperan dalam rehabilitasi sistem stomatognatik. Pemeliharaan yang optimal sangat penting untuk keberhasilan jangka panjang restorasi berbasis implan. Salah satu komplikasi yang dapat terjadi adalah peri-implantitis, yaitu kondisi patologis yang ditandai dengan peradangan jaringan ikat di sekitar implan dan kehilangan progresif tulang penyangga. Jika tidak ditangani, kondisi ini dapat menyebabkan kegagalan implan. Penelitian ini merupakan tinjauan pustaka (literature review) yang bertujuan untuk membahas efektivitas pengobatan non-bedah peri-implantitis. Data dikumpulkan melalui penelusuran di Google Scholar dengan kata kunci terkait, menghasilkan 15.700 artikel. Setelah dilakukan seleksi sesuai kriteria inklusi, dipilih artikel yang diterbitkan dalam lima tahun terakhir (2020–2024), berbahasa Inggris, teks lengkap, dan berupa original research, review, atau case report. Hasil dari tiga laporan kasus menunjukkan bahwa pendekatan non-bedah memberikan perbaikan klinis yang signifikan. Pada Kasus 1, setelah satu tahun, kedalaman probing berkurang menjadi 1,5–3 mm tanpa perdarahan. Pada Kasus 2, setelah enam bulan, tidak ditemukan tanda-tanda peradangan, dengan penurunan kedalaman probing sebesar 2,1 mm. Sedangkan pada Kasus 3, setelah enam bulan, terjadi resolusi inflamasi dengan kedalaman probing menjadi 2 mm dan peningkatan tingkat tulang berdasarkan radiograf. Semua pasien memiliki kebersihan mulut yang baik, tidak merokok, dan tidak memiliki penyakit sistemik yang tidak terkontrol. Secara keseluruhan, pengobatan non-bedah untuk peri-implantitis dapat memberikan hasil klinis yang positif dalam mengurangi kedalaman probing dan peradangan, terutama pada pasien dengan kontrol plak yang baik dan kondisi sistemik yang stabil.